The Role of Applying IAS and Iraqi Local Rules in Inventory Valuation and Their Impact on Tax Revenue: An Applied Study to A Sample of Iraqi Companies Listed in The Iraqi Stock Exchange - Gheni Jihad, Asaad; Abdullah Al Baaj, Qassim Mohammed; Hamzah albudairi, Asaad Hameed (Opción, 1970)
The problem of inventory valuation is one of the essential issues that raises scien- tific controversy among many accountants because of the multiplicity of local and international accounting standards through the valuation methods emanating from them. This leads to different results and effects on the financial income statement and the balance sheet of the company, which affects the tax revenues due to them. Accounting organizations and professional associations have confirmed that the inventory component has a significant and significant impact on the financial state- ments. The objective of the research is to examine the International Accounting Standard(IAS) No.2 ( the amended international standard) and the Iraqi Local Ac- counting Rule No. 5 related to the choice of inventory valuation methods and their impact on costing the value of the inventory at the end of the accounting period and its disclosure in the financial statements and comparing the effect of the methods used for evaluating the inventory according to the International and Local Account- ing Standards and that effect on the tax revenues of the companies in a product of the companies of the industry sector. The statistical analysis of the article has been based on FIFO, LIFO, and WAC methods of inventory valuation. The reason be- hind choosing such methods is related to the fact that they are the most commonly used measure for valuating inventories by most of the Iraqi industrial companies. The research has reached to a number of conclusions, the most important of which is that the application of the weighted average cost method proposed by the local accounting standard for Iraqi companies leads to more tax revenues compared with the other party. The researcher has reached a number of recommendations, the most important of which is that the application of companies first to the incoming and outgoing methods on the goods and merchandises with large prices achieve more accounting profitability compared to the average cost, which increases the tax revenue.